2021
DOI: 10.1155/2021/5526179
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Regulatory Role of lncRNA-miRNA-mRNA Axis in Amyotrophic Lateral Sclerosis: An Integrated Bioinformatics Analysis

Abstract: Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease that primarily affects motor neurons, causing muscle atrophy, bulbar palsy, and pyramidal tract signs. However, the aetiology and pathogenesis of ALS have not been elucidated to date. In this study, a competitive endogenous RNA (ceRNA) network was constructed by analyzing the expression profiles of messenger RNAs (mRNAs) and long noncoding RNAs (lncRNAs) that were matched by 7 ALS samples and 4 control samples, and then a protein-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…This model allows assessing how the different ncRNAs can interact together and affect the molecular pathogenesis of disease (Sardina et al, 2017). On this subject, Liu et al (2021) created a ceRNA network with the aim of making a molecular characterization of the ALS development and providing promising targets for clinical treatment. The study made it possible to understand that the regulation of MALAT1 plays an important role in the development of the disease.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
See 3 more Smart Citations
“…This model allows assessing how the different ncRNAs can interact together and affect the molecular pathogenesis of disease (Sardina et al, 2017). On this subject, Liu et al (2021) created a ceRNA network with the aim of making a molecular characterization of the ALS development and providing promising targets for clinical treatment. The study made it possible to understand that the regulation of MALAT1 plays an important role in the development of the disease.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
“…In this context, it is important to note that recent studies showed that lncRNA and mRNA can compete for binding to miRNAs and this interaction can play a role in different diseases, including ALS ( Liu et al, 2021 ). The potential cross-talk between miRNA-lncRNA-mRNA can be investigated by means of competitive endogenous RNA (ceRNA) network analysis.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
See 2 more Smart Citations
“…Bioinformatics analyses and computational studies highlighted the importance of unraveling altered gene pathways in ALS [ 95 , 96 , 97 , 98 , 99 ]. Concordantly, several efforts were made to match and functionally link miRNAs and their target genes through integrative approaches in ALS-associated model systems.…”
Section: Noncoding Rna Landscapementioning
confidence: 99%